Help-Seeking Behavior and Related Mental Health Promotion Programs in Southeast Asian Youth: A Systematic Literature Review - Octavia, Gladys; Doorbar, James A; Chan, Kallista (UI Scholars Hub, 2025)
Mental health issues are a prominent burden among adolescents and young adults in Southeast Asia, compounded by reluctance to seek help and low treatment rates. This mixed-method systematic review analyzed help-seeking profiles (preference, facilitators, and barriers) and evaluated implemented help-seeking programs. Data were sourced from electronic databases, hand-searched local databases, conference proceedings, and grey literature. Study selection followed PRISMA 2020 guidelines, focusing on 1) adolescents (10–19 years) and young adults (18–26 years) in Southeast Asia who were not receiving mental health care, 2) assessing help-seeking behavior, and 3) evaluating programs to increase help-seeking. A total of 16 articles were identified. Help-seeking behavior in Southeast Asian youth was shaped by mental health literacy and stigma (including attitudes from family, peers, and the wider community). Program effectiveness was mixed, with improvement often lacking significant differences from control groups or failing to persist at follow-up. These findings emphasized the need for more community-level and upstream policy interventions alongside individual-level interventions to improve mental health literacy and stigma. Developing interventions requires methodological improvements in help-seeking research, and ultimately, accessible and trustworthy mental health services are crucial to sustaining progress.